EFISIENSI PEMUPUKAN P TERHADAP PERTUMBUHAN DAN PRODUKSI TANAMAN JAGUNG (Zea mays L.) PADA TANAH ANDISOL DAN ULTISOL - Ardian Tambunan; Fauzi Fauzi; Hardy Guchi (Universitas Sumatera Utara, 2014)
ABSTRACTAn experimental research was done to measure the nutrient use efficiency (NUE) of Phosphorus (P)in Andisols and Ultisols. The research was conducted in Screenhouse and Research and TechnologyLaboratory, Faculty of Agriculture, University of North Sumatera from September 2012 until July2013. It was arranged in Non-factorial Randomized Block Design with 6 dosages of PhosphorusFertilizer (SP-36) in Andisols and Ultisols (0; 0,4; 0,8; 1,2; 1,6; and 2,0 grams of SP-36/plant). The intertreatments effects were analyzed using DMRT.The results showed thatRecovery Efficiency (RE) and Agronomic Efficiency (AE) in Ultisols are higher than in Andisols,meanwhile Physiological Efficiency (PE) in Andisols is higher. RE and AE were decreased as aresult of increasing dosage of SP-36 meanwhile PE was increased. The best treatment in Andisolsand Ultisols is 0,8 grams SP-36/plant. In Andisols, productivity of maize at that treatment is 109,23grams/plant (7,28 tons/Ha); RE (11,55%); PE (576,67 grams dry weight cob of maize /g P2O5);and AE (66,68 grams dry weight cob of maize /g P2O5). In Ultisols, productivity of maize at thattreatment is 67,30 grams/plant (4,48 tons/Ha); RE (15,16%); PE (589,29 grams dry weight cob ofmaize /g P2O5); and AE (88,94 grams dry weight cob of maize /g P2O5)Key words : Nutrient Use Efficiency (NUE), phosphorus (P), andisols, and ultisols